MENINGKATKAN PEMAHAMAN MODERASI BERAGAMA BERBASIS AL-QUR’AN DAN HADIS GURU-GURU MADRASAH IBTIDAIYAH “MI” KOTA TANJUNGPINANG KEPULAUAN RIAU - Islamiyah, Islamiyah; Maheran, Siti (Wahana Islamika Jurnal Studi Keislaman, 2025)
This study aims to analyze the improvement of the understanding of Madrasah Ibtidaiyah (MI) teachers in Tanjungpinang City regarding religious moderation based on the Qur'an and Hadith after being given mentoring and training. The research method used is qualitative with a descriptive approach, involving in-depth interviews, classroom observations, and documentation studies of the teaching materials used in the madrasah. The results of the study show that before the training, most teachers have a limited understanding of the concept of religious moderation and tend to see it as a form of reducing religious values. After participating in the training, teachers better understand that religious moderation is a balance in religion, a fair attitude, and respect for differences. Classroom observations show that teachers are beginning to apply open discussion methods and a more inclusive approach in teaching. Several madrasas have also begun to develop policies that encourage the application of moderation values in learning. Despite the increase in understanding, challenges such as the need for advanced guidance and more systematic integration in the curriculum remain obstacles.